From Complementarity to Disruption: Romanian – Russian Trade in the Era of Sanctions - Andreea - Emanuela DRAGOI; Paul CALANTER; Cornelia NEAGU (Communications of International Proceedings, 2025)
As a member of the European Union (EU), Romania aligned with the EU sanctions regime imposed on the Russian Federation following its illegal and unprovoked military invasion of Ukraine in February 2022. The enforcement of these sanctions—most visible in trade flows but extending to energy, finance, and related sectors—triggered a fundamental shift in bilateral economic relations. Against this complex geopolitical backdrop, this paper examines bilateral trade flows before and after the imposition of sanctions, with particular attention to the energy sector, where EU embargoes had a major impact during 2023–2024. The methodology relies on a comparative analysis of bilateral imports and exports for the period 2021–2024 (based on Eurostat data) to capture the effects of sanctions on economic cooperation between the two countries. The findings reveal a sharp contraction in trade, culminating in the near disappearance of energy exchanges and a marked decline in machinery and equipment exports, traditionally Romania’s main exports to the Russian Federation. While sanctions have reshaped bilateral ties from complementarity to near discontinuity, the analysis also underscores that cooperation opportunities could re-emerge, provided the Russian Federation respects international law and Ukraine’s sovereignty.
Keywords: Russian Federation; Romania; bilateral trade; international sanctions